First-year students’ communication apprehension in learning French as foreign language - Darmawangsa, Dante; Sukmayadi, Vidi; Yahya, Azizul Halim (Universitas Pendidikan Indonesia, 2020)
Learning a foreign language and being first-year students at the same time can be challenging as they struggle to make the transition in learning a new language and adjusting to their new lives as a university student. Students have to deal with not only the academic challenges but also the adaptation challenge since they are making a transition to their new day to day life on campus. One of the significant challenges students frequently faces as a foreign language learner is a lack of communication confidence, which can turn into a hampering factor for their academic achievements. This mixed-methods study aimed to examine students’ communication apprehension (CA) level and explore factors that contributed to their current level of CA. In this paper, the authors measured the level of CA in 57 first-year students of French Language departments in an Indonesian university. Quantitative data was analysed via McCroskey’s Personal Report of Communication Apprehension (PRCA-24). Qualitative questions explored how the first-year students perceived their senses of experiencing the communication apprehension. In addition, the qualitative thematic analysis was utilised to analyse the qualitative data. The findings indicated a moderate level of CA in most of the first-year studentssuch as fear of negative evaluation which was considered as the leading cause of the students’ high level of anxiety., Meanwhile, while prior knowledge and a supportive teacher-student relations were appraised as the main foundation of the low level of CA students.